The PENGARUH ELECTRONIC WORD OF MOUTH DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI CITRA MEREK (STUDI PADA PENGGUNA SMARTPHONE OPPO DI UNIVERSITAS HKBP NOMMENSEN MEDAN): PENGARUH ELECTRONIC WORD OF MOUTH DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN MELALUI CITRA MEREK (STUDI PADA PENGGUNA SMARTPHONE OPPO DI UNIVERSITAS HKBP NOMMENSEN MEDAN) - Sirait, Estauryna; Damanik, Hanna Meilani; Purba, Elvis Fresly; Naibaho, Krismanto Erick Tobush; Matondang, Vinsensius (Jurnal Ecoment Global, 2023)
This study aims to determine and analyze the effect of electronic word of mouth and price perceptions on purchasing decisions through brand image (Study on OPPO smartphone users at HKBP University Nommensen Medan). This research approach method uses quantitative methods with a sampling technique that is purposive sampling, with a sample of 100 respondents. To analyze the results of this study using path analysis (path analysis). The research results show 1). Electronic word of mouth has a positive and significant effect on purchasing decisions for OPPO smartphone users at HKBP Nommensen University Medan. 2). Price perception has a positive and significant effect on purchasing decisions for OPPO smartphone users at HKBP Nommensen University Medan. 3). Electronic word of mouth has a positive and insignificant effect on purchasing decisions through brand image on OPPO smartphone users at HKBP University Nommensen Medan. 4). Price perception has a positive and insignificant effect on purchasing decisions through brand image on OPPO smartphone users at HKBP Nommensen University Medan. 5). Electronic word of mouth and price perceptions together have a positive and insignificant effect on purchasing decisions through brand image on OPPO smartphone users at HKBP University Nommensen Medan.